Has Latin American Inequality Changed Direction?: Looking Over the Long Run - Bértola, Luis; Williamson, Jeffrey (Springer Nature, 2017)
Development Economics; Economic Growth; Social Structure, Social Inequality; Political Economy; Latin American Culture